2018
DOI: 10.1007/s12094-017-1819-7
|View full text |Cite
|
Sign up to set email alerts
|

A SUVmax-based propensity matched analysis of stereotactic body radiotherapy versus surgery in stage I non-small cell lung cancer: unveiling the role of 18F-FDG PET/CT in clinical decision-making

Abstract: The study found a superior PFS after surgery while OS and LRC did not differ between SBRT and surgery. Surgery should be recommended for tumor of high SUV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…For DFS, RFS or PFS, we included twelve relative studies in our meta-analysis (15,18,21,22,24,25,30,31,37,44,45,47). Eight studies de ned DFS, RFS or PFS as the time from treatment procedure until tumor recurrence or death (15,18,21,22,31,44,45,47), showing superior outcomes after surgery (matched studies: HR, 0.60;95% CI, 0.46-0.79; P=0.000; Figure E3, B).…”
Section: Primary Analysis: Results Of Survival Outcomes Of Surgery Versus Sbrtmentioning
confidence: 99%
See 1 more Smart Citation
“…For DFS, RFS or PFS, we included twelve relative studies in our meta-analysis (15,18,21,22,24,25,30,31,37,44,45,47). Eight studies de ned DFS, RFS or PFS as the time from treatment procedure until tumor recurrence or death (15,18,21,22,31,44,45,47), showing superior outcomes after surgery (matched studies: HR, 0.60;95% CI, 0.46-0.79; P=0.000; Figure E3, B).…”
Section: Primary Analysis: Results Of Survival Outcomes Of Surgery Versus Sbrtmentioning
confidence: 99%
“…Eight studies de ned DFS, RFS or PFS as the time from treatment procedure until tumor recurrence or death (15,18,21,22,31,44,45,47), showing superior outcomes after surgery (matched studies: HR, 0.60;95% CI, 0.46-0.79; P=0.000; Figure E3, B). Three studies de ned RFS or PFS as the time from the rst day of diagnosis to the date of tumor recurrence (25,30,37), but the pooled outcome of matched studies demonstrated no signi cantly difference between SBRT and surgery (HR, 0.61;95% CI, 0.34-1.08; P=0.091; Figure E3, B).…”
Section: Primary Analysis: Results Of Survival Outcomes Of Surgery Versus Sbrtmentioning
confidence: 99%
“…A total of 7,330 studies were identified from the databases, among which 54 were included in the full-text evaluation. Fifteen retrospective studies were included in this meta-analysis ( 11 , 12 , 15 - 27 ) ( Figure 1 ). All the included studies were of moderate quality at least.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies reported OS ( 11 , 12 , 15 - 27 ). The pooled HR showed that surgery was associated with a significantly higher OS than SBRT (HR =1.81; 95% CI, 1.72–1.90; P=0.000; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation